PENGALAMAN KERJA SEBAGAI PEMODERASI PENGARUH TINGKAT PENDIDIKAN PADA EFEKTIVITAS PENGENDALIAN INTERNAL - Mulihartini, Ni Kadek; RM, Ketut Muliartha (E-Jurnal Akuntansi, 2016)
The supervisors are required to have sufficient competence includes the level of education according to the watchdog function and work experience in cooperative where supervisors are expected to be able to assess and correct policies and cooperative operational processes with the aim of increasing the effectiveness of existing internal controls. The sampling method used is a non-probability method by using purposive sampling with criteria that cooperatives active status, has implemented RAT per March 31, 2015, and has been operating for more than two years. The sample used in this study of 33 savings and credit cooperatives. Data was collected by distributing questionnaires and analysis techniques using regression analysis without and with moderating variable. Based on the results of the analysis showed that the level of education a positive influence on the effectiveness of internal controls and found that work experience was not able memerlemah relationship of education level on the effectiveness of internal control of credit unions in Badung.
Keywords: Level of Education, Work Experience, Internal Control Effectiveness